Biosorption of Methylene Blue from Aqueous Solution Using Mixed Algae - Abbas Najim, Aya; A. Mohammed, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
A mixture of algae biomass (Chrysophyta, Cyanophyta, and Chlorophyte) has been investigated for its possible adsorption removal of cationic dyes (methylene blue, MB). Effect of pH (1-8), biosorbent dosage (0.2-2 g/100ml), agitated speed (100-300), particle size (1304-89μm), temperature (20-40˚C), initial dye concentration (20-300 mg/L), and sorption–desorption were investigated to assess the algal-dye sorption mechanism. Different pre-treatments, alkali, protonation, and CaCl2 have been experienced in order to enhance the adsorption capacity as well as the stability of the algal biomass. Equilibrium isotherm data were analyzed using Langmuir, Freundlich, and Temkin models. The maximum dye-sorption capacity was 26.65 mg/g at pH= 5, 250 rpm, 89μm, 25˚C, and 50 mg/L as initial concentration. Four kinetic models were tested, pseudo first order, pseudo second order, intra- particle diffusion and Elovich model. Taking into account the analysis of the (SSR and X2), the data were best fitted to Temkin isotherm model. The pseudo-second order with higher coefficient of determination fitted the data very well. Thermodynamic parameters (ΓG0, ΓH0, ΓS0, Ea and S*) at temperature ranges of 293–313 K demonstrated that biosorption is an endothermic, spontaneous reaction and higher solution temperature favors MB removal by adsorption onto algae biomass. Results show that adsorption- desorption process lasts for five cycle before losing its efficiency and the recovery efficiency increased up to 80.52%.